2021
DOI: 10.1021/acs.jpclett.1c01553
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Growth of Urchin Manganese Sulfide Anchored Three-Dimensional Graphene (γ-MnS@3DG) on Carbon Cloth as a Flexible Asymmetric Supercapacitor

Abstract: In energy storage-device it is highly crucial to develop durable electrode materials having high specific capacitance and superior energy density without disturbing its inherent flexibility. Herein, we demonstrate three-dimensional graphene oxide decorated monodispersed hollow urchin γ-MnS (γ-MnS@3DG) via proficient one-step solvothermal method. The designed material delivers a remarkable capacitance of 858 F g −1 at 1 A g −1 . A flexible solid state asymmetric supercapacitor (ASCs) device assembled using surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…77 In addition, the decoration of the γ-MnS urchin surface with graphene flakes has improved the cyclic stability up to 95% due to the faster dissipation of the interfacial heat as well as chemical protection and avoidance of the shrinkage/swelling of active materials. 15 The mechanical characteristics and flexibility of the hybrid device have been examined under rigorous bending and twisting conditions, as illustrated in Figure 4f. It has been observed that there is no significant shape change in the CV curve at rigorous bending angles (0, 90, and 135°) as well as under the twisting condition, signifying the impressive mechanical stability and superior flexibility of the ASC device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…77 In addition, the decoration of the γ-MnS urchin surface with graphene flakes has improved the cyclic stability up to 95% due to the faster dissipation of the interfacial heat as well as chemical protection and avoidance of the shrinkage/swelling of active materials. 15 The mechanical characteristics and flexibility of the hybrid device have been examined under rigorous bending and twisting conditions, as illustrated in Figure 4f. It has been observed that there is no significant shape change in the CV curve at rigorous bending angles (0, 90, and 135°) as well as under the twisting condition, signifying the impressive mechanical stability and superior flexibility of the ASC device.…”
Section: Resultsmentioning
confidence: 99%
“…As supercapacitors offer a specific power density, rapid charge and discharge process, and long-term durability, thus they have emerged as a popular system for certain applications in vehicles, cranes, emerging hybrid automobiles, G-series high-speed trains, and so on. , Nevertheless, supercapacitors are mostly made of a carbonaceous matrix and have some fatal drawbacks of delivering low energy density (∼10 Wh kg –1 ) in modern commercial applications due to a low potential window and limited electrochemically active surface functionality. ,, To overcome this issue, since last decade, asymmetric supercapacitors (ASCs) are assembled by different positive and negative electrode materials to successfully modulate the energy density without disturbing their power density. Currently, researchers have focused on transition metal-based compounds as a positive electrode and carbon-based materials as a negative electrode to enhance the voltage window and overall capacitance of supercapacitors. Out of which, transition metal phosphides (TMPs) can be investigated as one of the best valuable electrode materials in the fields of electrocatalysis, batteries, supercapacitors, and other energy device applications. , It is due to rich valences, weak ionic bond due to a lower electronegativity, and superior electronic conductivity of TMPs that make them environmentally stable, kinetically favorable for faster charge transport, and sustainable under high applied potentials. , Thus, TMPs have emerged as new battery-type electrode materials and gained more attention because they can improve the specific capacity along with the better rate capability of devices as compared to other electroactive materials. …”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al added reduced graphene oxide (rGO) to a g-MnS@3DG//3DG@CC composite, significantly decreasing the Ohmic and charge transfer resistance of the composite. 24 However, the application of rGO/CC composites in electrochemical sensors is still limited. In particular, the sensing action mechanism of rGO in the composites needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al added reduced graphene oxide (rGO) to a γ-MnS@3DG//3DG@CC composite, significantly decreasing the Ohmic and charge transfer resistance of the composite. 24…”
Section: Introductionmentioning
confidence: 99%
“…The unique 3D structure can provide optimal channels for rapid ion transport, thus accelerating the diffusion of electrolyte in the electrode material as well as shortening the diffusion pathway of ions in the electrochemical process. 24 For example, Wang et al reported a high-performance self-supported supercapacitor electrode (NiCoMnS 4 ) on CC, and the electrode delivered a high specific discharge capacity of about 2470.4 F g −1 at 1 A g −1 and high-rate performances of 910.2 F g −1 even at 32 A g −1 . 25 Hao et al prepared 3D hierarchical structure ZnO@C@NiO on CC, which yielded a higher specific capacity of 677 F g −1 at 1.43 A g −1 and an improved cycling stability (capacity remain 71% after 5000 cycles).…”
mentioning
confidence: 99%